2016
DOI: 10.9790/1684-1304040105
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Annealing of CdMnTe Material Being Developed for Nuclear Radiation Detection Applications

Abstract: Cadmium manganese telluride (CdMnTe) is one of the semiconductor materials with potential applications at room-temperature for nuclear and radiological detection. CdMnTe crystals grown by Bridgman technique are prone to tellurium inclusions and related defects that limit their performance as X-rays and gamma-rays detectors. The major reason for this is that they are grown in a tellurium-rich environment. These defects could trap charges that are generated by X-rays and gamma rays thereby degrading the charge t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It was found in the late 1990s that the crystal quality and electron charge colletion improves with the transition from CdTe to Cd1-xZnxTe (x ≈ 0.1-0.2) solid solution, but other problems remain. The new search for X/γ-ray detector materials continues, and Cd1-xMnxTe solid solutions deserve special attention due to their material properties [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It was found in the late 1990s that the crystal quality and electron charge colletion improves with the transition from CdTe to Cd1-xZnxTe (x ≈ 0.1-0.2) solid solution, but other problems remain. The new search for X/γ-ray detector materials continues, and Cd1-xMnxTe solid solutions deserve special attention due to their material properties [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to improve the crystal quality, researchers adopt post-growth annealing to reduce or eliminate these defects. However, few studies about the annealing of CMT crystals have been reported [7][8][9][10]. Generally, one annealing method only contains one step.…”
Section: Introductionmentioning
confidence: 99%